OPTIMALISASI SDM BERBASIS POTENSI LOKAL MELALUI PENDAMPINGAN KEWIRAUSAHAAN MENUJU DESA BERDIKARI DAN BERDAMPAK DI DESA CIKAMUNDING KECAMATAN CILOGRANG KABUPATEN LEBAK PROVINSI BANTEN - Sudiharto Sudiharto; Feby Arma Putra; Kholilah Kholilah; Ari Dominggo; Nunu Aisyah (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
Cikamunding Village, Cilograng District, Lebak Regency, Banten Province has various local potentials that can be developed to improve community welfare. However, limited knowledge of entrepreneurship, business management, marketing and resource management Humans become an obstacle in utilizing this potential. This Community Service Activity (PKM) aims to optimize human resources based on local potential through an entrepreneurial mentoring program towards an independent and impactful village. The methods used include socialization, training, mentoring and evaluation. The targets of the activity are MSMEs, youth groups, housewives and village officials. The results of the activity showed an increase in participants' understanding of entrepreneurship, business management, digital marketing, and product development based on local potential. This program also encourages the formation of an entrepreneurial spirit and increases community capacity in developing sustainable productive businesses. Thus, potential-based entrepreneurship assistance Localization can be an effective strategy in realizing self-sufficient villages and providing an economic impact on the community.